Mitragynine: a review of its extraction, identification, and purification methods - Amrianto; Sumail Sidik Ode Ishak; Nanda Putra; Syefira Salsabila; Laode Muhammad Ramadhan Al Muqarrabun (Institut Teknologi Bandung, 2021)
Mitragynine is one of the dominant alkaloids present in Mitragyna speciosa. The compound possesses several pharmacological properties such as antinociceptive, anti-inflammatory, and anti-cancer. Studies have reported various methods in extracting mitragynine, both conventional and renewable technology combined with acid-base techniques for the enrichment and purification of mitragynine from M. speciosa. Several chromatography and spectroscopy instruments such as HPLC, LC-MS, GC-MS, and NMR have been used to identify mitragynine and its content in both the extract and fraction mixtures. In this review, we aim to provide insight on how the methods of extraction, purification, and identification of mitragynine have been developed over the last few decades. This report shows comparison among the various approaches in extracting mitragynine and points out the facts that different methods gave different yields of the compound.